Genetic diversity of Pongamia pinnata (Millettia pinnata, aka. malapari) populations in Java Island, Indonesia - AAM AMINAH; SUPRIYANTO SUPRIYANTO; ANI SURYANI; ISKANDAR Z SIREGAR (Society for Indonesian Biodiversity, 2017)
Aminah A, Supriyanto, Suryani A, Siregar IZ. 2017. Genetic diversity of Pongamia pinnata (Millettia pinnata, aka. malapari) populations in Java Island, Indonesia. Biodiversitas 18: 677-681. One of the promising tree species to be utilized as biodiesel legume in Indonesia is malapari (Pongamia pinnata (L.) Pierre). The tree grows naturally along the North and South Coasts of Java Island. Malapari is now subjected to an initial breeding program, but its population diversity in Indonesia is not known yet. The objective of this study was to estimate genetic diversity in Java Island, namely populations of Carita, Batukaras, Kebumen, Alas Purwo National Park and Baluran National Park. RAPD markers were used to study the genetic diversity using the following DNA primers: OPL-11, OPAH-15, OPAO-01, OPAB-14 and OPAH-13. Results showed that DNA fragment lengths ranged from 250 to 1000 bp with a variable number of polymorphic bands, ranging between 13-24. Based on these RAPD markers, the population in Baluran was considered as a potential diversity center of malapari in Java, whereas the population in Kebumen was found to have the lowest genetic diversity. In general, the average genetic diversity within an population was lower than that among the populations. Cluster analysis of genetic similarity in five malapari population resulted in separation into two main clusters, the first group consisted of four populations (i.e., Carita, Batukaras, Kebumen and Alas Purwo). The other cluster was only one population only, namely Baluran.